2020
DOI: 10.3390/ijerph17176325
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Physical Activity in Middle-Aged and Older Adults in Rural South Africa: Levels and Correlates

Abstract: Little is known about physical activity (PA) levels and correlates in adults from rural settings in South Africa, where a rapid increase in the number of older people and marked disparities in wealth are evident, particularly between those living in rural and urban areas. This paper describes levels of self-reported PA in rural South African men and women and examines factors associated with meeting PA guidelines. Global Physical Activity Questionnaire (GPAQ) data from the Health and Aging in Africa: Longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…These findings from our study are reflective of current data and trends among adults across 22 SSA countries [63,67]. However, although the decline in physical activity with age is reflective of that seen in other populations, the levels of physical activity in older people in our sample are still higher than those seen in other populations in Africa [68]. Any proposed interventions relating to physical activity should consider age-adapted leisure activities to address physical inactivity across all age groups (more especially in older ages), and in those who are unemployed, retired or whose occupations do not involve physical activity.…”
Section: Discussionsupporting
confidence: 73%
“…These findings from our study are reflective of current data and trends among adults across 22 SSA countries [63,67]. However, although the decline in physical activity with age is reflective of that seen in other populations, the levels of physical activity in older people in our sample are still higher than those seen in other populations in Africa [68]. Any proposed interventions relating to physical activity should consider age-adapted leisure activities to address physical inactivity across all age groups (more especially in older ages), and in those who are unemployed, retired or whose occupations do not involve physical activity.…”
Section: Discussionsupporting
confidence: 73%
“…Findings from the HAALSI study in rural South African adults over the age of 40 years identified age as a significant correlate of self-reported physical activity with adults over the age of 70 years to be less likely to meet physical activity guidelines than those between 40 and 49 years of age (52).…”
Section: Discussionmentioning
confidence: 96%
“…In the current study, this seems to be more marked for both volume (ENMO) and higher-intensity physical activity (MVPA) in older men and women (between 60 and 72 yr of age). Findings from the Health and Aging in Africa: a longitudinal study of an INDEPTH community in South Africa study in rural South African adults older than 40 yr identified age as a significant correlate of self-reported physical activity with adults older than 70 yr to be less likely to meet physical activity guidelines than those between 40 and 49 yr of age (50).…”
Section: Discussionmentioning
confidence: 99%